New Insights into the Control of Pulsatile GnRH Release: The Role of Kiss1/Neurokinin B Neurons - Navarro, Víctor M. (Frontiers in Endocrinology, 2012)
Gonadotropin-releasing hormone (GnRH) is the ultimate output signal of an intricate network of neuroendocrine factors that, acting on the pituitary, trigger gonadotropin release. In turn, gonadopropins exert their trophic action on the gonads to stimulate the synthesis of sex steroids thus completing the gonadotropic axis through feedback regulatory mechanisms of GnRH release. These feedback loops are predominantly inhibitory in both sexes, leading to tonic pulsatile release of GnRH from puberty onwards. However, in the female, rising levels of estradiol along the estrous cycle evoke an additional positive feedback that prompts a surge-like pattern of GnRH release prior to ovulation. Kisspeptins, secreted from hypothalamic Kiss1 neurons, are poised as major conduits to regulate this dual secretory pathway. Kiss1 neurons are diverse in origin, nature and function, convening distinct neuronal populations in two main hypothalamic nuclei: the arcuate nucleus (ARC) and the anteroventral periventricular nucleus (AVPV). Recent studies from our group and others point out Kiss1 neurons in the ARC as the plausible generator of GnRH pulses through a system of pulsatile kisspeptin release shaped by the coordinated action of neurokinin B (NKB) and dynorphin A (Dyn) that are co-expressed in Kiss1 neurons (so-called KNDy neurons). In this review, we aim to document the recent findings and working models directed towards the identification of the Kiss1-dependent mechanisms of GnRH release through a synoptic overview of the state-of-the-art in the field.